Answer:
(-5, -2)
Explanation:
3x+4y=-23
x=3y+1
since we have what x is, we need to subsitute
3( 3y+1) + 4y= -23
no we need to multiply the number inside the parenthesis by 3
9y + 3 + 4y= -23
combine like terms ( add the numbers or variables that look alike)
9y+4y is 13y
13y+3= -23
since we need to get the y alone we need to subtract 3 on both sides since its the opposite of adding
13y+3-3=-23-3
13y= -26
now we divide 13 on both sides to get Y alone
13y/13= -26/13
y= -2
now since we have y we need to substitute it to find x
x= 3y+1
x= 3( -2) +1
now we mutliply 3 with -2
x= -6 +1
x=-5
those are ur answers
y= -2
x= -5
hope this helped:D